Changes in method for obtaining better outcomes in the recruitment of synthetic drug users. (October 2014) - Remy, Lysa; Von Diemen, Lisia; Surratt, Hilary L.; Kurtz, Steven P.; Pechansky, Flavio
<x xml:space="preserve">Abstract</x> Objective: To describe the problems encountered and resolved in the course of using respondent-driven sampling (RDS), targeted canvassing (TARC), and ethnographic fieldwork (EFW) to recruit ecstasy and/or lysergic acid diethylamide (LSD) users. Method: This study is nested within a larger project designed to investigate the course of drug use, sexual risk behaviors, and psychiatric comorbidities in 240 ecstasy/LSD users. Eligible participants were males and females with ages ranging from 18 to 39 years, who reported ecstasy and/or LSD use at least once during the 90 days prior to interview and were not under treatment for drug and alcohol problems. Strategies were implemented sequentially, over four-month time frames for each method, aiming at fulfilling study objectives. Results: The final sample included 174 participants (64.36% males). Eight (4.6%) were selected using RDS, 26 (14.94%) with TARC, and 140 (80.45%) using EFW. RDS recruited participants with a higher education level, employed, and with a higher monthly income. Conversely, a higher frequency of drug usage and a higher number of drugs ever used were evident among participants selected via EFW. Conclusions: Different recruitment techniques reached different types of participants. EFW showed the best performance, granting access to the largest number of participants and with a higher number of drugs ever used. Both RDS and TARC required more time to recruit participants and yielded a lower number of eligible subjects. Participants recruited via RDS had a higher socioeconomic level but also a shorter lifetime history of drug use.